The influence of cylindrical charge geometry on the velocity of blast-driven projectiles in one dimension - Qi, Ruixuan (University of Cape Town, 2020)
The impact of improvised explosive devices (IEDs) on the safety of civilians can be devastating, especially when solid objects are inserted into the explosives. These inserts are propelled at high speed and increase the lethality of an IED detonation. Due to the wide range of possible IED configurations, a fundamental understanding of momentum transfer from explosives to the solid inserts is required. This project investigated the influence of charge geometry on the velocity of a 5 mm diameter stainless steel ball bearing. The ball bearing was half-buried and centrally placed on the at face of a cylindrical charge which was detonated centrally on the opposite face. The geometric parameters of interest were the charge diameter and the charge aspect ratio (length/diameter). Investigations were carried out in the project through blast and impact experiments as well as numerical simulations. The impact velocity of the explosively driven ball bearing was inferred using the impact crater depth on a witness plate. The correlation between crater depth and the impact velocity was determined using impact experiments which was performed using a gas gun. The average velocity (between detonation and impact) was captured by tracking the time of detonation and impact. The time of impact was recorded through a Hopkinson Pressure Bar (HPB) behind the witness plate. Additionally, the total axial impulse and the localised impulse, over the face of the HPB, were recorded by a ballistic pendulum and the HPB. Numerical simulations were conducted using a commercial software, Ansys Autodyn 18.0. The blast arrangement was simulated using a two-dimensional, axisymmetric model. The maximum velocity, average velocity, impact velocity, total axial impulse and localised impulse were 'extracted' from the simulations. The simulated velocities agreed well with experimental measurements, showing less than 2% variation. The deformed shape of the blasted ball bearings displayed similar characteristics to the model predictions. There were differences in the simulated impulse, with the numerical model predicting higher magnitudes but a less localised distribution. For a constant charge diameter, the bearing velocity increased in a nearly logarithmic manner with the increase in aspect ratio until a critical aspect ratio of <msqrt>3</msqrt>/2 was reached. At a constant charge mass, the bearing velocity decreased with the increase in charge diameter. The numerical model suggested that the influence of charge geometry on the bearing velocity was likely caused by the shape of the detonation pressure waves. The detonation pressure profile is sensitive to the charge aspect ratio and the diameter.